Pioneering social research : life stories of a generation - Thompson, Paul, 1935-; Plummer, Kenneth; Demireva, Neli, 1981- (Policy Press, 2021)
Presenting the landmark Pioneers life stories project, this one-of-a-kind book documents how modern social research in the UK was shaped. It combines a fascinating history of the generations who built outstanding and influential social research with a valuable resource for future research and teaching on methods.